Effects of acupuncture versus moxibustion on functional dyspepsia: a randomized clinical trial - Yangke Mao; Pan Zhang; Zhaoxuan He; Yuke Teng; Zilei Tian; Sha Yang; Kuan Fang; Wei Zhang; Yuting Wang; Tao Yin; Fang Zeng (Chinese Medicine)
Abstract Background Functional dyspepsia (FD) is a prevalent gastrointestinal disorder, despite its high prevalence and impact on quality of life, effective treatments are limited. Acupuncture and moxibustion, two complementary therapies based on traditional Chinese medicine, have shown potential in alleviating FD symptoms. However, the differences of acupuncture and moxibustion in FD are unclear. Methods A total of 144 eligible FD patients were enrolled and randomly assigned to either the acupuncture or moxibustion group to receive 20 treatment sessions. The primary outcome was the Short-Form Leeds Dyspepsia Questionnaire (SFLDQ) total score after 4 weeks of treatment. Secondary outcomes included SFLDQ symptom-specific score, Nepean Dyspepsia Life Quality Index etc. Linear mixed-effects model was used for analyses. Results There was no difference in SFLDQ total score after treatment with acupuncture compared with moxibustion (difference, 0.08[95% CI −0.634 to 0.794], p = 0.82), despite both groups were effective. However, the results of the secondary outcomes showed that compared with moxibustion, acupuncture was more effective in alleviating epigastric pain (difference, -0.318[95% CI −0.056 to −0.579], p = 0.017) and anxiety mood (difference, −2.893[95% CI −0.419 to −5.367], p = .022). On the other hand, moxibustion was more effective than acupuncture in reducing post-prandial fullness (difference, −0.3[95% CI −0.551 to −0.048], p = .02). The incidence of adverse events was similar between the groups. Conclusions Both the acupuncture and moxibustion groups showed significant improvement in FD symptoms. Although there were no significant differences between the groups at week 4 for the primary outcome, acupuncture exhibited greater improvement in addressing epigastric pain and reduction in anxiety symptoms while moxibustion demonstrated a larger reduction in improving post-prandial fullness. Choice of acupuncture and moxibustion should be tailored to the primary symptoms of FD patients to achieve optimal efficacy. Trial registration: Chinese Clinical Trial Registry (ID: ChiCTR2100049496). Graphical Abstract